PEMBAHARUAN HUKUM KELUARGA ISLAM DI BRUNEI DARUSSALAM - potabuga, humaira (Fakultas Syariah Institut Agama Islam Negeri Palu, 2020)
The renewal of Islamic family law in Muslim countries is making rapid progress. This is because the response to legal issues that occur due to the times. Some countries still retain the rule of law of the School they profess, others are absolutely completely free from Islamic law and choose to make modern law as a reference. While other countries are trying to reform the law with a legislative process so that the creation of permanent legal rules in carrying out Islamic family law. The direction of renewal is related to the issue of children and women's rights in marriage or inheritance.